Evaluation and driving factors analysis of agricultural green development level in Beijing from 1978 to 2022 - Liang, Lina; Huai, Heju; Tang, Xiumei (Frontiers in Ecology and Evolution, 2023)
： : Agricultural green development (AGD) plays an improtantimportant role in achievingplays important roles to achieve sustainable society. In order to analyze the stages and characteristics of AGD in Beijing, this study evaluates the AGD level of Beijing from 1978 to 2022 by using comprehensive evaluation method, coupled coupling coordination degree (CCD) and grey relational degree model (GRA), and This paper evaluates the AGD level of Beijing from 1978 to 2022 by means of comprehensive evaluation method, coupling coordination degree (CCD) and grey relational degree model (GRA) with the purpose of exploring relevant stages and characteristics, as well as analyzes the characteristics of different stages and the coupling relationship of various factors, and quantitatively calculates the driving factors offor AGD change. The results show that: 1) The AGD level of Beijing generally improved from 1978 to 2022, mainly involving four stages of steady rising, fluctuating, oscillating decreasing and rapid upgrading; 2) From 1978 to 2022, the level of AGD in Beijing gradually improved, and experienced four stages: steady rising stage, fluctuating stage, oscillating decreasing stage and rapid upgrading stage. 2) The CCD of the development subsystem of AGD, agricultural resource utilization, agricultural environment condition, agricultural industry development and farmers' living standard has been on the rise, and the coordination type of each subsystem has gradually changed from verge imbalance stage, reluctantly coordinated stage, primary coordinated stage to intermediate coordinated stage, and reached to good coordinated stage in 2019.3) The AGD level in of Beijing is influenced by economic development, industrial structure, urbanization, technological progress and agricultural structure. Finally, some policy suggestions to promote AGD in Beijing are put forward. The results can promoteThis paper is of great significance to promoting the green and sustainable development of agriculture in Beijing and provideprovides technical support and policy guidance for AGD in other regions.